Current and Emerging Inhaled Antibiotics for Chronic Pulmonary Pseudomonas aeruginosa and Staphylococcus aureus Infections in Cystic Fibrosis - Danni Li; Elena K. Schneider-Futschik (MDPI AG, 2023)
Characterized by impaired mucus transport and subsequent enhanced colonization of bacteria, pulmonary infection causes major morbidity and mortality in patients with cystic fibrosis (CF). Pseudomonas aeruginosa (P. aeruginosa) and Staphylococcus aureus (S. aureus) are the two most common types of bacteria detected in CF lungs, which undergo multiple adaptational mechanisms such as biofilm formation resulting in chronic pulmonary infections. With the advantages of greater airway concentration and minimized systemic toxicity, inhaled antibiotics are introduced to treat chronic pulmonary infection in CF. Inhaled tobramycin, aztreonam, levofloxacin, and colistin are the four most common discussed inhaled antibiotics targeting P. aeruginosa. Additionally, inhaled liposomal amikacin and murepavadin are also in development. This review will discuss the virulence factors and adaptational mechanisms of P. aeruginosa and S. aureus in CF. The mechanism of action, efficacy and safety, current status, and indications of corresponding inhaled antibiotics will be summarized. Combination therapy and the strategies to select an optimal inhaled antibiotic protocol will also be discussed.